Integrating academic and practical skills in tahfiz education: an evaluation of the assets 2024 program - Affendy Lee, Noor Azli; Abd Rahman, Nor Hanim; Wan Pazilah, Wan Muhammad Nurhabis (Universiti Teknologi MARA, Kedah, 2025)
The ASSETS (Academic and Skills Enhancement Through Strategic Training) 2024 program was designed to address the gap in integrating academic and practical skills within Tahfiz education, which traditionally focuses on Quranic memorization. Conducted over three days, the program involved 21 Tahfiz students aged 9 to 17 years, providing a balanced curriculum that included both academic subjects (English and Mathematics) and practical skills (Frisbee, hair cutting, ice cream making, and body massage). The study employed a pre- and post-program survey methodology to assess the impact of the program on the participants' skills. The results revealed significant improvements in practical skills, with notable progress observed in areas such as hair cutting (71.4%) and Frisbee (71.4%). However, the improvements in academic subjects were mixed, with 76.2% of students showing progress in English, but only 57.1% in Mathematics. These findings suggest that while the ASSETS program is effective in enhancing practical skills, further refinement in the teaching methods for academic subjects is needed. The study underscores the importance of a holistic approach in education, particularly in specialized settings like Tahfiz schools, to ensure students are well-equipped for diverse life challenges.